The Validity Handout about Proboscis Monkey (Nasalis larvatus) on Curiak Island as an Enrichment Material for the Concept of Biodiversity in High School - Rema Yulianti; Hardiansyah Hardiansyah; Mahrudin Mahrudin; Amalia Rezeki (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
Teaching materials in learning activities have an important meaning so that the learning process is easier and more effective. Local potential can be used as a source of learning to look at phenomena, events, and problems in an area or what is also called contextual learning. The handout is one of the teaching materials that is concise and makes it easier for students to understand learning. The research method used was to analyze the results of research on proboscis monkey (Nasalis larvatus) on Curiak Island by Zainudin and Rezeki, to be used as material for the development of proboscis monkey (Nasalis larvatus) handouts on Curiak Island with the Tessmer development model which was limited to the expert stage review (Expert Test). The validation test was carried out with experts consisting of 3 (three) validators with an overall validity value of 90.6% (very valid and fit for use without revision). Its validity is shown by the average assessment on the feasibility aspect of the content of 85.07% (very valid), the assessment of the feasibility of serving 91.25% (very valid), and the assessment of the language aspect of 87.14% (very valid).Abstrak Bahan ajar pada kegiatan pembelajaran memiliki arti penting, agar proses pembelajaran lebih mudah dan lebih efektif. Potensi lokal dapat dijadikan sumber belajar melihat pada fenomena, peristiwa, maupun permasalahan pada suatu daerah yang disebut dengan pembelajaran kontekstual. Handout merupakan salah satu bahan ajar yang ringkas dan memudahkan peserta didik memahami pembelajaran. Metode penelitian yang digunakan adalah menganalisis hasil penelitian tentang bekantan (Nasalis larvatus) di Pulau Curiak oleh Zainuddin dan Rezeki, untuk dijadikan bahan pengembangan handout bekantan (Nasalis larvatus) di Pulau Curiak dengan model pengembangan Tessmer yang dibatasi hanya pada tahap expert review (Uji Pakar). Uji validasi dilakukan olehn para ahli yang terdiri dari 3 (tiga) validator dengan nilai validitas keseluruhan yaitu 90,6% (sangat valid dan layak digunakan tanpa revisi). Kevalidan ditunjukkan oleh rata-rata penilaian pada aspek kelayakan isi 85,07% (sangat valid), penilaian aspek kelayakan penyajian 91,25% (sangat valid), dan penilaian aspek bahasa 87,14% (sangat valid).